Autenticação de origem de méis de Ortigueira - PR usando voltametria cíclica e eletrodos de carbono modificados - Anizelli, Camilla Pastore (2022)
Honey is a naturally sweet substance and is produced from the nectar of flowers. It is a food source rich in carbohydrates and consists of a mixture of sugars, mainly glucose and fructose. The geographic characteristics are of mechanical and mechanical analysis of a time factor, normally they are of geographic origin of analysis that demand a time factor. Electrical voltammetry can be used as an alternative analytical tool for authenticating honey samples, as it is a fast, instrumentally simple and inexpensive technique. The aim of this study was to apply a cyclic voltammetry for authentication of origin of metals from Ortigueira (Paraná – Brazil) using carbon mass electrodes modified with carbon oxide, iron oxide, copper oxide and carbon nanotubes. Controlled voltammograms were used using chemometric exploratory analysis and classification methods. The results of analysis of hierarchical groupings and in the graphs of scores in the analysis of graphite components formed a superior performance of the electrodes formed by 60% of epoxy resin and 40% of epoxy resin, in comparison to the other electrodes. The best classification model of the samples with the electronic language was also collected with data from the C60 with 2 latent variables, presenting a percentage of correct classification for the prediction set of 94.44%. The PLS-DA (partial least squares with analysis) using voltammograms discriminant to with the C60 electrode presented larger and mainly PLS-DA using the physicochemical data that resulted in a model of high sensitivity, however with low selectivity, that is, high false positive rates. Based on the electronic tongue and this being a fast method (about 5 minutes per sample) and low cost, this methodology can be implemented more frequently to verify the analysis of the geographical origin of honey sample.